Tick-Borne Pathogens in Questing Blacklegged Ticks (Acari: Ixodidae) From Pike County, Pennsylvania. Issue 5 (3rd August 2022) - Schwartz, Sarah; Calvente, Elizabeth; Rollinson, Emily; Sample Koon Koon, Destiny; Chinnici, Nicole
Abstract: Active surveillance was conducted by collecting questing ticks from vegetation through a 2-yr survey in Pike County, Pennsylvania. Over a thousand blacklegged ticks ( Ixodes scapularis Say) and American dog ticks ( Dermacentor variabilis Say) were collected. A single specimen of the following species was collected: lone star tick ( Amblyomma americanum L.), rabbit tick ( Haemaphysalis leporispalustris Packard), and an Asian longhorned tick ( Haemaphysalis longicornis Neumann). This study represents the largest county-wide study in Pennsylvania, surveying 988 questing I. scapularis adult and nymphs. Molecular detection of five distinct tick-borne pathogens was screened through real-time PCR at a single tick resolution. Respectively, the overall 2-yr adult and nymph prevalence were highest with Borrelia burgdorferi (Spirochaetales: Spirochaetacceae) (45.99%, 18.94%), Anaplasma phagocytophilum (Rickettsiales: Anaplasmataceae) (12.29%, 7.95%) where the variant-ha (8.29%, 3.03%) was overall more prevalent than the variant-v1 (2.49%, 4.17%), Babesia microti (Piroplasmida: Babesiidae) (4.97%, 5.30%), Borrelia miyamotoi (Spirochaetales: Spirochaetaceae) (1.38%, 1.89%), and Powassan virus lineage II [POWV]/deer tick virus (DTV) (2.07%, 0.76%). Adult and nymph coinfection prevalence of B. burgdorferi and B. microti (3.03%, 4.97%) and adult coinfection of B. burgdorferi and A. phagocytophilum or A. phagocytophilum and B. microti were significantly higher than the independent infection rate expected naturally. This study highlights the urgency to conduct diverse surveillance studies with large sample sizes to better understand the human risk for tick-borne diseases within small geographical areas.